THE CHARACTERISTICS OF SELF PURIFICATION OF CODE RIVER YOGYAKARTA - , Ariek Wisnu Wibisono, Dr. M. Pramono Hadi M,Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
One of the important aspects in this life is water, it supports human activities such as farm, fishery, industry and domestic use. One of the efforts to conserve and manage the water resources is to develop good water quality management. Code River is one of the rivers in Opak watershed that is flowing across the city in Yogyakarta. In fact, the quality and quantity of water in the river is becoming worse in time. The landuse change and over population problem causing waste water disposal to the river. To prevent further damage to the river, it needs to protect the sustainability of a river. The aim of this research is (1) to know Code Riverâs self-purification characteristics